(untitled) (African Human Mobility Review, 2021)
This paper is a contribution to our understanding of the intertwined economic and political crises in Zimbabwe and the crisis of xenophobia in South Africa. There have been few studies to date specifically examining the impact of xenophobic violence on Zimbabweans trying to make a living in the South African informal economy. The paper first provides a picture of Zimbabwean migrant entrepreneurship using survey data from a 2015 study of migrants in the informal economy. All of the Zimbabwean entrepreneurs interviewed in depth for the study in 2016 had either witnessed or been the victims of xenophobic violence or both. The interviews focused on the experience and impact of xenophobic violence on personal safety and business operations. The migrant accounts clearly demonstrate that they see xenophobia as a key driver of the hostility, looting and violence that they experience. The paper argues that the deep-rooted crisis in Zimbabwe, which has driven many to South Africa in the first place, makes return home in the face of xenophobia a non-viable option. Zimbabweans are forced to adopt a number of self-protection strategies, none of which ultimately provide insurance against future attack.